PENGARUH DAYA TARIK ENDORSER IKLAN PRODUK MODE BUSANA DI MAJALAH TERHADAP BODY DISSATIDFACTION PADA REMAJA PUTRI - Fitriana, Neni; Deliana, Sri Maryati (Intuisi : Jurnal Psikologi Ilmiah, 2012)
Abstrak. Penelitian ini merupakan penelitian kualitatif korelasional yang bertujuan untuk mengetahui pengaruh daya tarik endorser iklan produk mode busana di majalah terhadap body dissatisfaction pada remaja putri. Subjek pada penelian ini berjumlah 100 subjek. Teknik sampling yang digunakan adalah insidental sampling. Body dissatisfaction diukur dengan skala body dissatisfaction. Skala body dissatisfaction terdiri sari 39 aitem valid. Aitem valid tersebut mempunyai p < 0,05 yaitu rentanf signifikansi 0,000 sampai dengan 0,001. Skala body dissatisfaction mempunyai koefisiensi reliabilitas sebesar 0,928. Skala daya tarik endorser iklan produk mode busana di majalah terdiri dari 33 aitem valid. Aitem yang valid tersebut mempunyai p < 0,05 yaitu rentang signifikansi 0,000 sampai 0,001. Skala daya tarik endrorser iklan mempunyai koefisiensi reliabilitas sebesar 0,939. Uji korelasi menggunakan teknik korelasi product moment dan uji pengaruh digunakan analisis regresi menggunakan bantuan program SPSS 17 for windows.Hasil penelitian menunjukkan variabel body dissatisfaction pada remaja putri tergolong tinggi. Demikian juga variabel daya tarik endorser iklan produk mode busana di majalah yang juga tergolong tinggi. Hasil penelitian menunjukkan bahwa terdapat pengaruh antara body dissatisfaction dengan daya tarik endorser iklan produk mode busana di majalah dengan F sebesar 431.590 korelasi body dissatisfaction dengan daya tarik iklan endorser iklan produk di majalah diperoleh koefisien r = 0,903 dengan signifikansi atau p = 0,000. Dari hasil penelitin menunjukkan pengaruh daya tarik endorser terhadap body dissatisfaction dengan R square sebesar 81,5%.Hal tersebut menunjukkan bahwa ada pengaruh yang signifikan antara daya tarik iklan endorser iklan produk mode busana di majalah terhadap body dissatisfaction pada remaja putri di Universitas Negeri Semarang.Kata Kunci: daya tarik endorser iklan; body dissatisfaction; majalah; remaja putri Abstract. This research is based the existence of phenomenon that occurs in young women who experience body dissatisfaction, where young women are having negative thoughts and feeling dissatisfied eith the shape, size and weight.Body dissatisfaction has a negtive impact for the sufferer, such as: unhealthy dietary behaviors, eating disorders, cosmetic surgery and low self-esteem. One of the factors that cause body dissatisfaction is advertising a produk endorser attractiveness fashions whit thin bodies and high character displayed in the magazine. Yong women who are interested in advertising endorser body shape is the process of body identification and comparing the real with the idealized body, so they are prone to body dissatisfaction.            This study is correlational quantitative study aimed to determine the effect of endorser attractiveness fashions product advertising in magazines on body dissatisfaction in adolescent girls. Other research on this subject amounted to 100 subjects. Sampling technique used was incidental sampling. Body dissatisfaction was measured by the scale of body dissatisfaction. Body dissatisfaction scale consist of 39 item valid. It has a valid item p < 0.05 significance is the range of 0.000 to 0.001. Body dissatisfaction scale had reliability coefficient of 0.928. Endorser attractiveness scale product advertising in magazines fashions consisted of 33 item valid. It has valid item p < 0.05 significance is the range of 0.000 to 0.001. Endorser attractiveness scale advertising has reliability coefficient of 0.939. Correlation test using the product moment correlation technique and the influence of test used regression analysis using SPSS 17 for windows.The results showed variable body satisfaction in adolescent girls is high. Similarly, endorser attractiveness variable product advertising in magazines fashions also quite high. The results showed that there is influence between body satisfaction with product advertising endorser attractiveness fashions in the magazines with the F 431.590 for correlation with body satisfaction appeal endorser advertising product advertising in magazines coefficient r = 0.903 with a significance or p = 0.000. From the research results show the influence of advertising a product endorser attractiveness of body satisfaction in the magazines advertising with R square of 81.5%.            It is shown that there is significant influence between endorser attractiveness advertising product advertising magazines fashions of body satisfaction in adolescent girls at the Semarang State University.